Loyalitas Pelanggan Ayam Goreng Nelongso Bululawang: Peran Customer Experience, Kepercayaan, dan Lifestyle Halal - Putri, Stevany Amelia; Susyanti, Jeni; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the effect of Customer Experience, Trust, and Halal Lifestyle on Customer Loyalty at Ayam Goreng Nelongso Bululawang. This research is a quantitative study with data collection techniques using a questionnaire. The sample in this study amounted to 80 respondents. The sampling technique is using snowball sampling. Data processing using SPSS (Statistical Package For Social Sciences) with multiple regression analysis methods. The results of this study indicate that Customer Experience and Trust have a positive and significant effect on Customer Loyalty, while Halal Lifestyle has a positive but insignificant effect on Customer Loyalty. Keywords: Customer Experience, Trust, Lifestyle Halal, Customer Loyalty